2017
DOI: 10.1017/s1092852917000876
|View full text |Cite
|
Sign up to set email alerts
|

New medications for treatment-resistant depression: a brief review of recent developments

Abstract: There is a great unmet need for new medications with novel mechanisms of action that can effectively treat patients who do not benefit from standard antidepressant therapies. After a period in which it seemed as if the pharmaceutical pipeline for new antidepressants was going dry, the past decade has witnessed renewed interest, beginning with discovery of the antidepressant effects of ketamine. This article briefly highlights more recent research on ketamine and other investigational antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Mood disorders are chronic, recurrent, and debilitating mental illnesses that affect the lives of millions of people worldwide and are leading contributors to the global burden of disease 1,2 . Many patients are refractory to conventional therapies and the development of new drugs with novel mechanisms of action is crucial 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Mood disorders are chronic, recurrent, and debilitating mental illnesses that affect the lives of millions of people worldwide and are leading contributors to the global burden of disease 1,2 . Many patients are refractory to conventional therapies and the development of new drugs with novel mechanisms of action is crucial 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…The development of new antidepressants targeting novel pathways opens a promising perspective for the management of TRD [2]. And other way for management of TRD is ketamine that is a new antidepressants with pharmaceutical pipeline [26]. Sixty-two trials were identified in US and EU clinical trial registries that included six investigational compounds in recent phase III development and 12 others in recent phase II clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that VAP may have better effect for TRD. So many studies were carried out in china [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This also is the reasons that do meta-analysis to found magnesium valproate and antidepressants for therapy of treatment-resistant depression (TRD) in China is better or not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several potential therapies for TRD have emerged, starting with the discovery of the antidepressant effects of ketamine, and followed by a renewed interest in antidepressant drugs with novel mechanisms of action (eg, esketamine, rapastinel, ALKS-5461 [combination of buprenorphine and samidorphan], and scopolamine) 10,11. However, the long-term benefits and costs of these drugs are unknown, and there remains an unmet need for effective new therapies for patients with TRD.…”
Section: Introductionmentioning
confidence: 99%